2017
DOI: 10.1111/1759-7714.12547
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐to‐lymphocyte ratio predicts the prognosis of patients with non‐small cell lung cancer treated with surgery and postoperative adjuvant chemotherapy

Abstract: BackgroundMarkers of preoperative tumor immunity, such as platelet‐to‐lymphocyte ratio (PLR), have been reported to be prognostic factors for patients with various cancers. However, the relationship between PLR and the prognosis of non‐small cell lung cancer (NSCLC) patients treated with surgery and adjuvant chemotherapy as a multidisciplinary treatment is unknown.MethodsWe enrolled 327 NSCLC patients treated surgically with or without adjuvant chemotherapy (78 and 249 patients, respectively) at our hospital f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The neutrophil to lymphocyte ratio (NLR), the platelet to lymphocyte ratio (PLR) and the lymphocyte to monocyte ratio (LMR) are regarded as reliable markers of inflammatory processes, ongoing oncological patients. An elevated level of these ratios is a consequence of increased numbers of neutrophils, monocytes and platelets and/or a decreased number of lymphocytes, accompanying the neoplastic process (8)(9)(10).…”
Section: Original Articlementioning
confidence: 99%
“…The neutrophil to lymphocyte ratio (NLR), the platelet to lymphocyte ratio (PLR) and the lymphocyte to monocyte ratio (LMR) are regarded as reliable markers of inflammatory processes, ongoing oncological patients. An elevated level of these ratios is a consequence of increased numbers of neutrophils, monocytes and platelets and/or a decreased number of lymphocytes, accompanying the neoplastic process (8)(9)(10).…”
Section: Original Articlementioning
confidence: 99%
“…In recent years, studies have reported that platelets and lymphocytes play critical roles in the inflammatory process. Therefore, the platelet-to-lymphocyte ratio (PLR)—a novel inflammatory factor—has received research attention recently, as it may act as an indicator of inflammation8 in a wide spectrum of diseases, such as myocardial infarction,9 acute kidney injury (AKI),10 hepatocellular carcinoma11 and non-small cell lung cancer 12…”
Section: Introductionmentioning
confidence: 99%
“…NLR can also predict postoperative outcome after curative resection [ 12 – 14 ]. Platelet to lymphocyte ratio is also a prognostic marker in advanced NSCLC [ 15 17 ]. Moreover, lymphocyte to monocyte ratio (LMR) is an independent prognostic factor in NSCLC [ 18 ].…”
Section: Introductionmentioning
confidence: 99%